Analisis Implementasi Pelayanan dan Tenaga di Perpustakaan SLB Negeri Cicendo Berdasarkan Peraturan Perpustakaan Nasional Nomor 10 Tahun 2023 - Cahyani, Raisya Gita; Sinaga, Dian; Rohman, Asep Saeful (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The issuance of National Library Regulation Number 10 of 2023 concerning National Standards for Special School Libraries can be a reference to determine the suitability of the application of special school library components. The purpose of this study is to determine the analysis of service and staff components in the Special School (SLB) Negeri Cicendo Library based on the standards in National Library Regulation Number 10 of 2023. In this study, a qualitative research method with a descriptive approach was used. The results show that the SLB Negeri Cicendo Library had implemented 7 out of 13 indicators in the service and staff components of the library. Applied 2 indicators out of a total of 4 indicators in the library service component. Applied 5 indicators out of a total of 9 indicators in the library staff component.